2018
DOI: 10.3390/ph11010012
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Secretase ADAM10 Regulation: Insights into Alzheimer’s Disease Treatment

Abstract: ADAM (a disintegrin and metalloproteinase) is a family of widely expressed, transmembrane and secreted proteins of approximately 750 amino acids in length with functions in cell adhesion and proteolytic processing of the ectodomains of diverse cell-surface receptors and signaling molecules. ADAM10 is the main α-secretase that cleaves APP (amyloid precursor protein) in the non-amyloidogenic pathway inhibiting the formation of β-amyloid peptide, whose accumulation and aggregation leads to neuronal degeneration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 152 publications
(181 reference statements)
2
78
0
Order By: Relevance
“…Further, defects in CX3CR1-CX3CL1 signaling and ADAM10 have been identified to either enhance or suppress neurodegeneration in a variety of neurological disease models depending on the disease, insult, brain region, etc. 38,[61][62][63][64][65][66] . Here, we identify that neuronal ADAM10 is modulated in the cortex by sensory lesioning and disruption of ADAM10, CX3CL1 (an ADAM10 substrate), or CX3CR1 results in profound defects in microglial synaptic engulfment and synapse elimination following a peripheral sensory lesion known to dampen activity in the cortex 38,[64][65][66] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, defects in CX3CR1-CX3CL1 signaling and ADAM10 have been identified to either enhance or suppress neurodegeneration in a variety of neurological disease models depending on the disease, insult, brain region, etc. 38,[61][62][63][64][65][66] . Here, we identify that neuronal ADAM10 is modulated in the cortex by sensory lesioning and disruption of ADAM10, CX3CL1 (an ADAM10 substrate), or CX3CR1 results in profound defects in microglial synaptic engulfment and synapse elimination following a peripheral sensory lesion known to dampen activity in the cortex 38,[64][65][66] .…”
Section: Discussionmentioning
confidence: 99%
“…38,[61][62][63][64][65][66] . Here, we identify that neuronal ADAM10 is modulated in the cortex by sensory lesioning and disruption of ADAM10, CX3CL1 (an ADAM10 substrate), or CX3CR1 results in profound defects in microglial synaptic engulfment and synapse elimination following a peripheral sensory lesion known to dampen activity in the cortex 38,[64][65][66] . This mechanism is particularly intriguing in light of recent data in mouse models of Alzheimer's disease where changes in neural activity modulates microglial morphology, Aβ, and amyloid plaques 67,68 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have implicated that activation of α-secretase can induce unfavorable effects because ADAM proteins can increase the processing of other substrates, resulting in the promotion of tumorigenesis, tumor growth, and inflammation [13]. Thus, the importance of substrate-specific ADAM targeting has been highlighted in the AD research field to avoid side-effect [14]. Our data showed that E144 decreased the secreted level of TNF-α, ruling out the possibility that E144 might cause putative side-effects by increasing TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…α-Secretase can be a constitutive cleavage enzyme or be stimulated by several G protein-coupled receptors (GPCRs) activating drugs and several kinases such as protein kinase C (PKC), phosphatidyl-inositol 3-kinase, and mitogen-activated protein kinase [12,13]. Among three family members, ADAM10 is considered as sheddase for APP and other diverse cell-surface proteins, including cytokines, cell adhesion molecules (CAMs), and Notch [13,14]. In contrast, ADAM9 and ADAM17 are believed to undertake regulated APP cleavage [13,15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation